1011 Restless Legs Syndrome is Highly Prevalent in Long Term Care Residents with Alzheimer's Disease and Nighttime Agitation. (27th April 2018) - Richards, K C; Allen, R P; Bliwise, D L; Kovach, C R; Morrison, J; Gooneratne, N; Chittams, J; Huang, L; Fry, L; Rangel, A; Loera, A; Dominquez, D; et al.
Abstract: Introduction: Up to 66% of persons with Alzheimer's Disease (AD) have agitation, and these behaviors may vary such that they are more prevalent at night. We confirmed in preliminary studies that nighttime agitation (NA) was associated with RLS, and that persons with AD do not have the verbal and cognitive skills for the standard RLS diagnostic interview. We then developed and validated the Behavioral Indicators Test-Restless Legs (BIT-RL), a new instrument suitable for RLS diagnosis in persons with AD. We now report feasibility of the BIT-RL for diagnosing RLS and RLS prevalence in long-term care (LTC) residents with AD and nighttime agitation. Methods: Residents were referred by LTC staff not involved in data collection to participate in a clinical trial. Criteria for referral were nighttime agitation, AD, ability to swallow uncrushed medication, and a legally authorized representative for consent. 56 residents from 10 homes were referred, 28 were excluded because they did not meet trial inclusion criteria, and 28 were included (82.83 ± 8.01 yrs, 75% female). RLS diagnosis was made by consensus of: 1) MD sleep medicine, 2) MD geriatrics, and 3) PhD sleep medicine using the BIT-RL, 7 days of actigraphy, and medical history. Results: 24 (86%) were RLS+ (BIT-RL 9.25 ± 1.15), and 4 were RLS- (BIT-RL 1.50 ± 1.73). The most prevalent RLS behaviors were fidgeting, pushing like on a gas pedal, and pushing against a surface. Total sleep time was 251.30 ± 133.34 minutes in the RLS+ group versus 342.23 minutes ± 121.36 in RLS- group. Conclusion: The BIT-RL is a feasible diagnostic instrument for this population. RLS is highly prevalent in older adults with AD and agitated nighttime behaviors. Treatment of RLS may offer a viable alternative to antipsychotics and sedatives for treatment of agitation and sleep disturbance in this population. Support (If Any): NIA R01 AG051588, Arbor Pharmaceuticals (study drug only).